2018
DOI: 10.15282/jmes.12.4.2018.05.0351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inlet air temperature on SI engine fueled with diethyl ether-gasoline blends

Abstract: In this study the performance and emission characteristics of spark ignition genset engine fueled with gasoline and diethyl ether (DEE) blends are carried out. The DEE blends are varied from 3%, 6% and 9% by volume in gasoline. A four-stroke single cylinder constant speed spark ignition engine is used for the experiments. The variation in fuel consumption and exhaust emission with respect to two different inlet air temperatures are studied. The concentration of exhaust emissions such as HC, CO, NOx is observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Balaji et al, [14] concluded that fuel consumption increased with the increase of DEE addition at the same engine torque in a spark ignition engine. Kumar et al, [15] found that BSFC increased by 16% and 8.5% with 6% and 3% DEE fuel mixtures respectively at maximum engine load and 22°C inlet air temperature in a SI engine. They have stated that lower heating value of DEE resulted in higher BSFC.…”
Section: Fig 4 the Influences Of Dee On Sfc Versus Engine Speedmentioning
confidence: 99%
See 3 more Smart Citations
“…Balaji et al, [14] concluded that fuel consumption increased with the increase of DEE addition at the same engine torque in a spark ignition engine. Kumar et al, [15] found that BSFC increased by 16% and 8.5% with 6% and 3% DEE fuel mixtures respectively at maximum engine load and 22°C inlet air temperature in a SI engine. They have stated that lower heating value of DEE resulted in higher BSFC.…”
Section: Fig 4 the Influences Of Dee On Sfc Versus Engine Speedmentioning
confidence: 99%
“…At 4000 rpm, CO measured lower by about 0.67%, 3.39%, 10.61% and 11.11% with DEE10, DEE20, DEE30 and DEE40 according to pure gasoline. Kumar et al, [15] mentioned that CO reduced for base fuel, 3% DEE, 6% DEE and 9% DEE test fuels at 22°C inlet air temperature from 10% to 75% engine load in a spark ignition engine. Sezer [7] found lower CO emissions with ethanol, DEE fuel blends at middle and high engine loads compared to diesel.…”
Section: Fig 4 the Influences Of Dee On Sfc Versus Engine Speedmentioning
confidence: 99%
See 2 more Smart Citations